How to Produce Sheep's Cheese? Pastoralism vs. Intensification in the Slovak Mountains - Michel Lompech (Revue de Géographie Alpine)
This article traces the evolution of dairy sheep farming in Slovakia over the last century. The collectivist economy modernized sheep farming, which had stayed partly traditional, and was out of step with other agricultural sectors. The post-socialist transformation of the 1990s accelerated changes in livestock farming systems and cheese production methods. The intensification trajectories associated with the delivery of milk to dairies contrast with the revived ways of pastoralism.